Pengaruh Digital Entrepreneur Role Model dan Kreativitas terhadap Minat Berwirausaha Mahasiswa - Dimis, Vika Wapa Putri; Sakti, Norida Canda (Jurnal Maksipreneur, 2025)
Despite the increasing business opportunities created by technological advances, student interest in entrepreneurship during the digital era remains low. This study examines how Digital Entrepreneur Role Models and creativity influence students' interest in entrepreneurship. This study uses a quantitative method, including multiple linear regression and log-linear models, to analyze the data. The data were collected from questionnaires given to economics students in the 2022 cohort at Surabaya State University between October and November 2022. The analysis looked at how each variable affects students' interest in entrepreneurship, both individually and together. The findings show that both independent variables have a positive and significant impact on students' interest in starting a business. Digital entrepreneur role models help build students' confidence and drive to start a business, while creativity helps them come up with new business ideas and innovations. These results indicate that policymakers and schools should develop programs that foster digital entrepreneurship and promote student creativity. The unique aspect of this study is the integration of digital entrepreneur role models with creativity to understand how students engage in entrepreneurship within the digital age.